DEVELOPMENT OF THE CULTURE OF PSYCHOLOGICAL HEALTH OF TEACHERS IN THE PROCESS OF PROFESSIONAL IMPROVEMENT - Олексенко, Світлана; Савченко, Світлана (Modern engineering and innovative technologies, 2023)
The article highlights the relevance of supporting and preserving the psychological health of teachers in the process of professional growth. The development of the culture of psychological health of teachers is considered as an integral part of general c